Short-term growth and morphological responses to nitrogen availability and plant density in hybrid poplars and willows. (October 2015) - Mamashita, Takamitsu; Larocque, Guy R.; DesRochers, Annie; Beaulieu, Jean; Thomas, Barb R.; Mosseler, Alex; Major, John; Sidders, Derek
Abstract: Morphological characteristics of poplar and willow clones were determined in order to identify main characteristics leading to superior growth under increased plant competition with low or high nitrogen (N) availability. Seven hybrid poplar ( Populus spp. including one hybrid aspen) and five willow ( Salix spp.) clones were grown under greenhouse conditions for 13 weeks at three spacings (20 × 20, 35 × 35, and 60 × 60 cm) and two N levels (20 and 200 mg kg −1 ). The decrease in spacing from 60 to 20 cm reduced leaf area by 50% but clones had similar aboveground biomass per tree under all spacings, with increasing their height per unit leaf area. More productive clones had greater leaf area (+102%), leaf area per unit plant biomass (+12%) and lower root-to-shoot ratios (−27%) compared to less productive clones. There were positive relationships between leaf area and above-ground biomass per tree for both more and less productive clones. Compared to low N level and 60 cm spacing, trees growing in high N level and 20 cm spacing reached similar root collar diameter, crown width, and leaf area values and even greater height, suggesting that an addition of N could help mitigate negative effects of tree competition. Highlights: We examined Populus and Salix clones that can maximize biomass productivity under increased plant densities and nitrogen levels. Nitrogen plays an essential role in greater plant growth under increased plant densities. Greater productive clones had greater leaf area and leaf area ratio, and lower root-to-shoot ratio. There were different growth characteristics between Populus and Salix over a growing period. Short three month study period showed clonal differences in morphological characteristics, suggesting the possibility for early clone selection.